Evaluation of Free-operant Preference Assessment: Outcomes of Varying Session Duration and Problem Behavior. Issue 6 (November 2021) - Clay, Casey J.; Schmitz, Brittany A.; Clohisy, Anne M.; Haider, Aqdas F.; Kahng, SungWoo
Previous researchers have found brief versions of preference assessments correspond to outcomes of longer preference assessments, and that varying levels of problem behavior occur in different preference assessments. Researchers conducted two studies to examine 1-, 2-, and 5-min duration outcomes of the free-operant preference assessment and evaluated the correspondence between the shorter and longer session durations and to identify frequency of problem behavior at each duration. Researchers also assessed relative reinforcing efficacy of the highest preferred stimulus from the shortest duration sessions. Moderate to high correlations were found between the 1- and 2-min sessions and 1- and 5-min sessions across six of eight participants diagnosed with autism spectrum disorder in Study 1 and two of three participants in Study 2. Furthermore, all highest preference stimuli identified in the shortest duration assessment served as reinforcers. Researchers found problem behavior generally occurred more in longer duration sessions.